Grassland restoration in a changing world: consequences of restoration approaches and variable environments - Carter, Daniel Lanphier (Kansas State University, 2013)
The feasibility of restoration, which traditionally targets historical conditions, is questionable in the context of global change. To address this, my dissertation investigated (Chapter 2) the patterns of restoration establishment along a chronosequence of restored prairies with respect to nearby remnant prairies, (Chapters 3-4) responses of plant communities in restorations initiated using different methods (levels of species richness and sowing density) to drought, which is projected to increase in frequency, and (Chapters 5-6) the effects of propagule source and variation (mixing among sources) on restoration establishment and the generality of restoration outcomes across variable environments using reciprocal common gardens of multi-species restoration seedings. Chapter 2, published in Restoration Ecology, showed that restoration led to the recovery of desirable characteristics within several years, but restorations utilizing primarily fall-collected seeds likely diminished the representation of early phenology species, so biodiversity may be further enhanced by including early phenology species in seeding mixes. Chapters 3 and 4, published respectively in Ecological Applications and Applied Vegetation Science, examined the establishment of native plant communities after seeding and their responses to experimentally imposed drought. Both high seed mixture richness and high density seeding resulted in greater establishment of native, seeded species compared to low richness and low density treatments, and exotic species were less prevalent in high richness and high density treatments. However, we found little evidence of differential drought resistance, recovery, and resilience among treatments. This result coupled with increases in exotic species following drought suggest that other forms of active management may be needed to produce restored plant communities that are robust to climate change. Chapter 5 (published in Ecosphere) iii and Chapter 6 found that seed source affects individual species establishment, community structure, and productivity. However, there was no consistent advantage for any source, including local sources, across sites or species. This suggests that source effects on single species or effects observed at single locations should not be broadly generalized. Together, this dissertation shows that restoration can recover many characteristics of native prairies and that manipulation of seeding practices (seed mixture richness, seeding density, seed source) influence grassland establishment in terms of productivity, community structure, invasion, and the abundance and survival of individual species.
Keywords: Climate change; Tallgrass; Common garden; Local adaptation; Chronosequence; Biology (0306); Ecology (0329)